Effects of Moisture and Amphiphilic Compounds on the Oxidative Stability of Microwave‐Treated Corn Oil. Issue 3 (15th February 2021) - Na, HeeSun; Choi, Hyuk; Lee, YoonHee; Lee, JaeHwan
Abstract: Effects of moisture and amphiphilic compounds, including oleic acid, lecithin, and monoacylglycerols (MAGs), on the oxidative stability are evaluated in microwave‐treated corn oil. Moreover, the physical properties including critical micelle concentration (CMC) and moisture content are determined in oils treated by microwave irradiation. The CMC of lecithin and moisture content of oils decreases remarkably, whereas the temperature of the oil increases rapidly with microwave irradiation. The addition of lecithin results in increased moisture content significantly in the edible oils, whereas oleic acid and MAGs do not exhibit these effects. Primary oxidation products in all the oil samples increase, despite the type of amphiphilic compounds used. Corn oil containing oleic acid and samples with lecithin exhibits lower and higher p ‐anisidine values ( p‐ AV), respectively. Remarkably high moisture content in corn oils containing lecithin may contribute to the formation of volatile compounds and high p‐ AV. Collectively, moisture and amphiphilic compounds affect the degree of lipid oxidation in microwave‐irradiated bulk oils. Practical application : A microwave oven is an irreplaceable home appliance and is widely used in households nowadays. Effects of amphiphilic compounds and moisture on the oxidative stability are evaluated and it is found that the amphiphilic compounds in lipids affect heat transfer and oxidative stability of oils. The results of this study can provide fundamental insights into lipid oxidation in edible oils, and can provide a direction to the food industry with respect to the development of more efficient and safe methods for the preparation of microwavable foods. Abstract : Microwave irradiation on oxidative stability is determined in edible oils with amphiphilics. Microwave irradiation decreases critical micelle concentration and moisture content in oils. Added lecithin increases moisture content and accelerates volatile formations from microwaved oils. Moisture and amphiphilics affect rates of lipid oxidation in microwave‐irradiated corn oils. Shelf‐life of microwavable foods can be controlled by amphiphilics and moisture content.